Legalitas Kebijakan Afirmasi Pendidikan bagi Peserta Didik dari Daerah 3T di Indonesia : The Legality of Affirmative Action Policies in Education for Students from 3T Regions in Indonesia - Keysha Audina; Chisa Belinda Harahap (Journal of Indonesian Comparative of Syari'ah Law, 2026)
This study aims to analyze the legality of affirmative education policies for Indonesia’s disadvantaged, frontier, and outermost (3T) regions by examining the gap between legal norms and their implementation in society. Normatively, the research emphasizes that affirmative action constitutes a constitutionally legitimate instrument intended to achieve substantive equality and ensure fair and equitable access to education, particularly for marginalized communities. This study employs an empirical legal research method supported by secondary data analysis, including statutory regulations, policy documents, performance reports, and relevant scholarly works. The data are elaborated descriptively and qualitatively using Roscoe Pound’s concept of law as a tool of social engineering, integrated with Lawrence M. Friedman’s legal system theory. The findings indicate that, from a normative perspective, affirmative education policies possess a strong legal foundation; however, their implementation requires further evaluation due to various structural obstacles, such as limited inter-agency coordination, delays in scholarship disbursement, and a weak supporting legal culture. The results reveal a gap between law in books and law in action. The study concludes that the effectiveness of affirmative education policies in 3T regions requires the simultaneous strengthening of legal substance, legal structure, and legal culture to ensure sustainable and impactful improvements in equitable access to and quality of education